A magnetically controlled micro-nano robot and its manufacturing method and use

Magnetic micro-nano robots are prepared by coating magnetic material dispersion solution and lithography technology, which solves the problems of high equipment costs, complex operation and poor material versatility in the prior art, and achieves low-cost and efficient magnetron micro-nano robot preparation and fast directional motion capabilities.

CN115196585BActive Publication Date: 2025-03-04SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210614325.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-01
Publication Date
2025-03-04
Estimated Expiration
2042-06-01

AI Technical Summary

Technical Problem

In the manufacturing of magnetic control swims of achiral micro-nano robots, the prior art requires expensive large and high-end complex equipment, which is complex in operation and poor in versatility in plating magnetic materials, which is difficult to meet research and practical needs.

Method used

The magnetic layer is formed by coating a dispersed solution of magnetic material, and a magnetron micro-nano robot is prepared through photolithography, which avoids the use of high-end equipment and restriction material deposition methods, which is easy to operate and low cost.

Benefits of technology

It realizes a magnetron micro-nano robot that moves rapidly under the action of a magnetic field, reduces production costs, simplifies operations, and expands material selection, which is suitable for industrial large-scale preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115196585B_ABST
    Figure CN115196585B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of micro-nano robots, and in particular to a magnetically controlled micro-nano robot and a manufacturing method and use thereof. The manufacturing method of the magnetically controlled micro-nano robot comprises the following steps: coating a magnetic material dispersion solution on the surface of a substrate to form a magnetic layer; the magnetic material dispersion solution is Fe 3 O 4 A γ-butyrolactone (GBL) solution is prepared; a photoresist is coated on the surface of the magnetic layer, and photolithography is performed to obtain a magnetically controlled micro-nano robot. The manufacturing method of the present invention does not require the use of expensive large-scale high-end complex equipment, and is easy to operate. The obtained magnetically controlled micro-nano robot can move rapidly and directional under the action of a magnetic field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of micro-nano robots, and in particular relates to a magnetically controlled micro-nano robot and a manufacturing method and use thereof. Background Art

[0002] Micro-nano robots are a type of robots with micro-nano sizes that can be driven intelligently on a tiny spatial scale. They have potential application value in precision biomedicine, real-time sensor monitoring, micro-nano processing and manufacturing, pollution prevention and control, and environmental remediation.

[0003] At present, the intelligent driving methods of micro-nano robots mainly include chemical, magnetic field, sound wave and light driving. Among them, magnetic field driving has received extensive attention and research due to its advantages such as strong penetration. At present, the most common magnetic control device used to drive the movement of micro-nano robots is the Helmholtz three-dimensional coil system, which can provide a rotating uniform magnetic field. The movement in the rotating magnetic field usually requires the micro-nano robot to have a chiral spiral structure, such as a spiral micro-nano robot. However, due to the complex structural characteristics, the spiral micro-nano robot is difficult to achieve mass production. In 2014, Professor U KeiCheang studied and manufactured a simple three-bead structure of non-chiral micro-nano robots and verified its swimming performance under a rotating magnetic field. After that, Bradley J.Nelson used the simple two-dimensional plane structural characteristics of non-chiral micro-nano robots and used photolithography technology to realize the mass production of micro-nano robots, proving that simple processes, high throughput, and low cost can be used to manufacture non-chiral micro-nano robots with simple shapes that can swim under rotating magnetic fields.

[0004] In order to realize the magnetically controlled swimming of non-chiral micro-nano robots, it is necessary to load the micro-nano robots with magnetic materials. The current loading methods mainly include incident deposition method, electron beam evaporation and other methods. However, these methods have great defects. On the one hand, they require the use of specific large-scale high-end complex equipment, which is cumbersome to operate and costly; on the other hand, they have poor versatility for plated magnetic materials, and only a few magnetic materials can achieve this, which is far from meeting research and practical needs. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the first aspect of the present invention is to propose a method for making a magnetically controlled micro-nano robot, which method does not require the use of expensive large-scale high-end complex equipment, is easy to operate, and the magnetically controlled micro-nano robot can move quickly and directional under the action of a magnetic field.

[0006] The second aspect of the present invention is to propose a magnetically controlled micro-nano robot obtained by the above-mentioned manufacturing method.

[0007] The third aspect of the present invention is to propose the application of the magnetically controlled micro-nano robot.

[0008] Specifically, the present invention adopts the following technical solutions:

[0009] The first aspect of the present invention is to provide a method for manufacturing a magnetically controlled micro-nano robot, comprising the following steps:

[0010] A magnetic material dispersion solution is coated on the surface of the substrate to form a magnetic layer; the magnetic material dispersion solution is a γ-butyrolactone (GBL) solution of Fe3O4;

[0011] A photoresist is coated on the surface of the magnetic layer and photolithography is performed to obtain a magnetically controlled micro-nano robot.

[0012] The method for preparing a magnetically controlled micro-nano robot according to the present invention has at least the following beneficial effects:

[0013] Fe3O4 is a common magnetic material, but since the magnetic layer of a magnetron micro-nano robot is generally prepared by incident deposition, electron beam evaporation and other methods, such methods not only require the use of expensive large-scale high-end complex equipment and are complicated to operate, but also have restrictions on the types of materials. Not all magnetic materials can be made into thin films by incident deposition and electron beam evaporation. The present invention prepares the magnetic layer by a coating method. Compared with the existing incident deposition method, electron beam evaporation and other methods, it not only does not require the use of expensive large-scale high-end complex equipment, but is also easy to operate, and can successfully apply Fe3O4 to the production of magnetron micro-nano robots. At the same time, the present invention uses γ-butyrolactone (GBL) as a dispersant, which can well disperse Fe3O4 to form a uniform and stable dispersed solution. A uniform magnetic layer can be obtained by a simple coating method, so that the magnetron micro-nano robot can move quickly and directional under the action of a magnetic field.

[0014] In addition, the manufacturing method of the present invention prepares the magnetic layer first and then coats the photoresist for photolithography, thereby avoiding the problem of first coating the photoresist and then coating the magnetic layer, which makes it impossible to prepare the required pattern structure using photolithography technology.

[0015] In some examples of the present invention, the concentration of Fe3O4 in the magnetic material dispersed solution is 20-500 mg / mL, such as 20 mg / mL, 30 mg / mL, 40 mg / mL, 50 mg / mL, 80 mg / mL, 100 mg / mL, 200 mg / mL, 300 mg / mL or 500 mg / mL, preferably 100 mg / mL.

[0016] In some embodiments of the present invention, the method of applying the magnetic material dispersion solution includes any one or more of spin coating, spray coating, roller coating, and brushing, preferably spin coating. The spin coating speed is 100-1000rpm, such as 100rpm, 250rpm, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm or 1000rpm, preferably 500rpm.

[0017] In some embodiments of the present invention, before coating the substrate surface with the magnetic material dispersion solution, a step of coating a sacrificial layer on the substrate surface is also included. Preferably, the sacrificial layer includes a dextran layer. The dextran film layer is soluble in water. After the magnetically controlled micro-nano robot is manufactured, it is placed in water, the dextran film layer dissolves, and the robot can be peeled off from the substrate without damage.

[0018] In some embodiments of the present invention, the preparation method of the dextran layer is: coating a dextran solution on the surface of the substrate. The mass fraction concentration of the glucose solution is 1-20wt%, such as 1wt%, 5wt%, 8wt%, 10wt%, 18wt% or 20wt%, preferably 5wt%.

[0019] In some embodiments of the present invention, the method of coating the dextran solution includes any one or more of spin coating, spray coating, roller coating, and brushing, preferably spin coating. The spin coating speed is 100-1000rpm, such as 100rpm, 250rpm, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm or 1000rpm, preferably 500rpm.

[0020] In some embodiments of the present invention, after forming the magnetic layer, the step of baking the magnetic layer is further included. The temperature of baking the magnetic layer is 40-100° C., such as 40° C., 50° C., 65° C., 75° C., 80° C., 95° C. or 100° C., preferably 65° C. By baking the magnetic layer, the magnetic layer and the dextran layer can be more closely combined.

[0021] In some embodiments of the present invention, the magnetic layer is baked for 30-1200 seconds, such as 30 seconds, 60 seconds, 120 seconds, 300 seconds, 500 seconds, 600 seconds, 800 seconds, 1000 seconds or 1200 seconds, preferably 300 seconds.

[0022] In some embodiments of the present invention, the photolithography step specifically includes: coating a photoresist on the surface of the magnetic layer, exposing and developing the photoresist, and completing the photolithography.

[0023] In some embodiments of the present invention, after the magnetic layer is photolithographically processed, the magnetic layer forms a non-chiral structure, such as an "L"-shaped structure or an approximately "L"-shaped structure, the angle of which is ≥90° and less than 180°, for example, 90-179°, such as 90°, 98°, 100°, 110°, 179°, etc., preferably 120°.

[0024] In some embodiments of the present invention, the photoresist coating method includes any one or more of spin coating, spray coating, roller coating, and brush coating, preferably spin coating. The photoresist spin coating speed is 500-4000rpm, such as 500rpm, 800rpm, 1000rpm, 2000rpm, 2500rpm, 3000rpm, 3500rpm or 4000rpm, preferably 1000rpm.

[0025] In some embodiments of the present invention, after the photolithography is completed, a step of baking the magnetically controlled micro-nano robot is further included, and the mutual adhesion between the magnetic layer and the photoresist can be strengthened by baking.

[0026] In some examples of the present invention, the temperature for baking the magnetically controlled micro-nano robot is 40-100°C, such as 40°C, 50°C, 65°C, 75°C, 80°C, 95°C or 100°C, preferably 65°C.

[0027] In some examples of the present invention, the baking time of the magnetically controlled micro-nano robot is 30-1200 s, such as 30 s, 60 s, 120 s, 300 s, 500 s, 600 s, 800 s, 1000 s or 1200 s.

[0028] In some embodiments of the present invention, after the magnetron micro-nano robot is baked, a step of dissolving the sacrificial layer is also included. After the sacrificial layer is dissolved, the magnetron micro-nano robot can be peeled off from the substrate without damage. Ultrasound can be used to assist in the dissolution process to accelerate the dissolution. In the case where the sacrificial layer is a dextran layer, it can be directly dissolved with water.

[0029] In some examples of the present invention, the substrate includes any one or more of a silicon wafer, a glass wafer, a metal wafer, and a ceramic wafer, preferably a silicon wafer.

[0030] In some examples of the present invention, the average thickness of the magnetic layer is 0.1-10 μm, for example, 0.1 μm, 0.12 μm, 0.5 μm, 2 μm, 8 μm or 10 μm.

[0031] Preferably, the overall average thickness of the achiral micro-nano robot is 5-35 μm, for example, 5 μm, 10 μm, 12 μm, 15 μm, 20 μm, 25 μm, 30 μm or 35 μm.

[0032] The second aspect of the present invention is to provide a magnetically controlled micro-nano robot prepared by the above method.

[0033] In some examples of the present invention, the magnetically controlled micro-nano robot includes a magnetic layer and a photoresist layer stacked on top of each other.

[0034] In some examples of the present invention, the instantaneous motion speed of the magnetically controlled micro-nano robot in a three-dimensional uniform rotating magnetic field of 5 mT is ≥ 0 μm / s, preferably ≥ 1 μm / s, more preferably ≥ 4 μm / s, and even more preferably ≥ 10 μm / s. The instantaneous motion speed of the magnetically controlled micro-nano robot in a three-dimensional uniform rotating magnetic field of 5 mT can reach up to 26 μm / s or more.

[0035] The third aspect of the present invention is to provide the application of the magnetically controlled micro-nano robot in precision biomedicine, real-time sensing monitoring, micro-nano processing and manufacturing, pollution protection and management or environmental restoration. The magnetically controlled micro-nano robot prepared by the present invention moves rapidly and directional in a magnetic field, and can be intelligently driven on a micro-space scale, so it has potential application value in the fields of precision biomedicine, real-time sensing monitoring, micro-nano processing and manufacturing, pollution protection and management or environmental restoration.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The present invention prepares the magnetic layer through a simple stacking coating technology. Compared with the prior art methods such as incident deposition method and electron beam evaporation, it does not require the use of expensive large-scale high-end complex equipment, has a lower production cost, is simple and easy to operate, and can be industrially mass-produced in a uniform manner.

[0038] At the same time, the present invention uses γ-butyrolactone (GBL) as a dispersant, which can disperse Fe3O4 well to form a uniform and stable dispersed solution. A uniform magnetic layer can be obtained through a simple coating method, so that the magnetically controlled micro-nano robot can move quickly and directional under the action of a magnetic field.

[0039] The magnetically controlled micro-nano robot manufactured by the present invention can realize rapid directional movement under the control of a three-dimensional uniform rotating magnetic field. After interacting with an external magnetic field, it will obtain the movement characteristics of a chiral magnetic structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The schematic diagram and microscope image of the structure of the achiral magnetically controlled micro-nano robot of Example 1;

[0041] Figure 2 This is a microscope image of the achiral magnetically controlled micro-nano robot of Example 2;

[0042] Figure 3This is a microscope image of the achiral magnetically controlled micro-nano robot of Example 3;

[0043] Figure 4 The motion of the non-chiral magnetically controlled micro-nano robot in Example 3 at different times under a magnetic field;

[0044] Figure 5 This is a microscope image of the achiral microrobot of Comparative Example 1;

[0045] Figure 6 It is a microscope picture of the magnetic layer prepared by using different dispersants in Comparative Example 2;

[0046] Figure 7 Microscope images of magnetic layers prepared at different Fe3O4 concentrations. DETAILED DESCRIPTION

[0047] The technical scheme of the present invention is further described below in conjunction with specific examples. The raw materials used in the following examples, unless otherwise specified, can all be obtained from conventional commercial sources; the processes used, unless otherwise specified, all adopt conventional processes in the art.

[0048] Example 1

[0049] This embodiment prepares a magnetically controlled micro-nano robot, which belongs to a non-chiral magnetically controlled micro-nano robot, and includes the following steps:

[0050] 1) Coating magnetic layer

[0051] The clean silicon wafer was plasma treated to obtain a hydrophilic surface, and then 5wt% dextran solution was spin-coated at an angular speed of 500rpm for 60s. After spin coating, it was placed on a hot plate at 95℃ and baked for 4min until dry. Then, 20mg / mL of magnetic Fe3O4 GBL dispersion solution was coated at an angular speed of 1000rpm for 60s, and after spin coating, it was placed on a hot plate at 65℃ and baked for 60s until dry to form a magnetic layer.

[0052] 2) Photolithography

[0053] After step 1), the surface of the magnetic layer dried is coated with SU-8 2005 photoresist, with a spin coating angular speed of 1000rpm for 60s. The coated silicon wafer is baked at 65°C for 4min, the sample is placed on the stage, a mask is placed on the surface of the glue, and it is exposed to ultraviolet light for 60s. The exposed sample is baked at 65°C for 2min. The sample is developed in a developer and rinsed with acetone, fished out and blown dry, then baked at 65°C for 10min, and finally placed in deionized water for peeling to obtain an approximately "L"-shaped non-chiral magnetically controlled micro-nano robot.

[0054] The structural schematic diagram and microscope image of the non-chiral magnetically controlled micro-nano robot are shown in Figure 1 As shown in (a) and (b), the figure shows that the surface of the micro-nano robot is loaded with a uniform black Fe3O4 coating. The overall thickness (height h) of the micro-nano robot is 7.9μm, the length a is 200μm, the width b is 100μm, and the angle θ is greater than 90° and less than 180°.

[0055] Example 2

[0056] This embodiment prepares a magnetically controlled micro-nano robot, which belongs to a non-chiral magnetically controlled micro-nano robot. The main difference between the preparation method and that of Example 1 is that the concentration of the GBL dispersed solution of Fe3O4 in step 1) is increased to 100 mg / mL. Specifically, the following steps are included:

[0057] 1) Coating magnetic layer

[0058] The clean silicon wafer was plasma treated to obtain a hydrophilic surface, and then 5wt% dextran solution was spin-coated at an angular speed of 500rpm for 60s. After spin coating, it was placed on a hot plate at 95℃ and baked for 4min until dry. A 100mg / mL GBL dispersion solution of magnetic Fe3O4 was coated at an angular speed of 200rpm for 60s, and after spin coating, it was placed on a hot plate at 65℃ and baked for 600s until dry to obtain a magnetic layer.

[0059] 2) Photolithography

[0060] After step 1), the surface of the magnetic layer dried is coated with SU-8 2005 photoresist, with a spin coating angular speed of 1000rpm for 60s. The coated silicon wafer is baked at 65°C for 4min, the sample is placed on the stage, a mask is placed on the surface of the glue, and it is exposed to ultraviolet light for 60s. The exposed sample is baked at 65°C for 2min. The sample is developed in a developer and rinsed with acetone, fished out and blown dry, then baked at 65°C for 10min, and finally placed in deionized water for peeling to obtain an approximately "L"-shaped non-chiral magnetically controlled micro-nano robot.

[0061] Microscope images of the non-chiral magnetically controlled micro-nano robot are shown below. Figure 2 As shown in the figure, the surface of the micro-nano robot is loaded with a uniform black Fe3O4 coating, and the black Fe3O4 coating is darker in color than that of Example 1. Its overall thickness is 26.7 μm, and its length, width, and angle are the same as those of Example 1.

[0062] Example 3

[0063] This embodiment prepares a magnetically controlled micro-nano robot, which belongs to a non-chiral magnetically controlled micro-nano robot. The main difference between the preparation method and that of Example 1 is that the concentration of the GBL dispersed solution of Fe3O4 in step 1) is increased to 500 mg / mL. Specifically, the following steps are included:

[0064] 1) Coating magnetic layer

[0065] The clean silicon wafer was plasma treated to obtain a hydrophilic surface, and then 5wt% dextran solution was spin-coated at an angular speed of 500rpm for 60s. After spin coating, it was placed on a hot plate at 95℃ and baked for 4min until dry. 500mg / mL of magnetic Fe3O4 GBL dispersion solution was coated at an angular speed of 100rpm for 60s, and after spin coating, it was placed on a hot plate at 65℃ and baked for 1200s until dry.

[0066] 2) Photolithography

[0067] After step 1), the surface of the magnetic layer dried is coated with SU-8 2005 photoresist, with a spin coating angular speed of 1000rpm for 60s. The coated silicon wafer is placed at 65°C for 4min, the sample is placed on the stage, a mask is placed on the surface of the glue, and it is exposed to ultraviolet light for 60s. The exposed sample is placed at 65°C for 2min. The sample is developed in a developer and rinsed with acetone, removed and blown dry, then baked at 65°C for 10min, and finally placed in deionized water for stripping to obtain a non-chiral magnetically controlled micro-nano robot.

[0068] Microscope images of the non-chiral magnetically controlled micro-nano robot are shown below. Figure 3 As shown in the figure, it can be seen that the black Fe3O4 coating on the surface of the micro-nano robot is darker than that in Example 2, its overall thickness is 34.2 μm, and its length, width and angle are the same as those in Example 1.

[0069] Test Case

[0070] In this test example, the performance of the achiral micro-nano robots prepared in Examples 2 and 3 was tested:

[0071] The non-chiral magnetically controlled micro-nano robot can move in the fluid after applying a magnetic field, and has different movement modes under different magnetic field control. The specific performance tests are as follows:

[0072] (1) Sports performance test

[0073] The non-chiral micro-nano robot obtained in Example 2 is placed in deionized water, and a magnetic field is applied (the magnetic field generator is a three-dimensional Helmholtz coil system, and the magnetic field generated is a three-dimensional uniform rotating magnetic field with a magnetic field size of 5mT), and a motion performance test is performed to check whether it can move, and observe the motion speed and stability. This test proves that the non-chiral magnetically controlled micro-nano robot has good motion performance in deionized water. The motion conditions (position, speed V) of the non-chiral magnetically controlled micro-nano robot at different times are shown in FIG. Figure 4 As shown ( Figure 4 The scales of the small figures are the same), and it can be manipulated by magnetic field, which further proves that it is loaded with magnetic materials and can move in the magnetic field. And according to records, the maximum instantaneous movement speed of this non-chiral magnetically controlled micro-nano robot reached 26.9493μm / s.

[0074] (2) Flow channel simulation test

[0075] The achiral micro-nano robot in Example 3 was placed in different types (different shapes) of flow channels, a magnetic field (magnetic field size of 5 mT) was applied, and it was controlled to move to a specified position, and its motion stability was observed. This test proves that the micro-nano robot can be controlled by a magnetic field for directional movement, and further proves that the prepared achiral micro-nano robot has magnetic control performance.

[0076] The test results show that the magnetically controlled micro-nano robot prepared according to the method of the present invention can move rapidly and directionally in a magnetic field and can be intelligently driven on a tiny spatial scale. Therefore, it has potential application value in the fields of precision biomedicine, real-time sensor monitoring, micro-nano processing and manufacturing, pollution prevention and control, or environmental restoration.

[0077] Comparative Example 1

[0078] The difference between this comparative example and Example 1 is that the GBL dispersion solution of magnetic Fe3O4 is not spin-coated, and the specific steps are as follows:

[0079] The clean silicon wafer was plasma treated to obtain a hydrophilic surface, and then 5wt% dextran solution was spin-coated at an angular speed of 500rpm for 60s. After spin coating, it was placed on a hot plate at 95℃ and baked for 4min until dried. SU-8 2005 photoresist was applied at an angular speed of 1000rpm for 60s. The silicon wafer after the coating was placed at 65℃ and baked for 4min, the sample was placed on the stage, the mask was placed on the top of the glue surface, and it was exposed to ultraviolet light for 60s. The exposed sample was placed at 65℃ and baked for 2min. The sample was developed in a developer and rinsed with acetone, fished out and blown dry, and finally placed in deionized water for peeling to obtain a non-chiral microrobot.

[0080] The microscope image of the resulting achiral microrobot is shown below. Figure 5As shown in the figure, it can be seen that there is no black Fe3O4 magnetic coating on the surface of the micro-nano robot, and it is only a transparent structure composed of SU-8 2005 photoresist, with a thickness of 7.6μm, and its length, width and angle are the same as those in Example 1.

[0081] Comparative Example 2

[0082] The difference between this comparative example and Example 2 is that the GBL in the GBL dispersion solution of magnetic Fe3O4 is replaced by ethyl acetate. The specific steps are as follows:

[0083] The clean silicon wafer was plasma treated to obtain a hydrophilic surface, and then 5wt% dextran solution was spin-coated at an angular speed of 500rpm for 60s. After spin coating, it was placed on a hot plate at 95°C and baked for 4min until dried. GBL and ethyl acetate dispersion solutions of magnetic Fe3O4 were prepared at a concentration of 100mg / mL, respectively, vortexed for 5min and ultrasonically dispersed for 20min, and then spin-coated at an angular speed of 1000rpm for 60s. After spin coating, it was placed on a hot plate at 65°C and baked for 1200s until dried to obtain a magnetic layer, which was then observed under a microscope.

[0084] The microscopic image of the magnetic layer is shown in Figure 6 b. For ease of comparison, Figure 6 A shows a microscope image of the magnetic layer of Example 2 under the same magnification conditions. Figure 6 It can be seen that the Fe3O4 nanoparticles with GBL as dispersant are evenly dispersed, while the Fe3O4 nanoparticles in the solution with ethyl acetate as dispersant have large agglomerates and poor dispersion uniformity. The dispersion uniformity of GBL on Fe3O4 is better than that of ethyl acetate.

[0085] Comparative Example 3

[0086] In this comparative example, the magnetic layer was spin-coated with GBL dispersions of different Fe3O4 concentrations, and the specific steps were as follows:

[0087] The clean silicon wafer was plasma treated to obtain a hydrophilic surface, and then 5wt% dextran solution was spin-coated at an angular speed of 500rpm for 60s. After spin coating, it was placed on a hot plate at 95°C and baked for 4min until dried. GBL solutions of Fe3O4 with concentrations of 10mg / mL, 100mg / mL and 600mg / mL were prepared, vortexed for 5min and ultrasonically dispersed for 20min before spin coating at an angular speed of 1000rpm for 60s. After spin coating, it was placed on a hot plate at 65°C and baked for 1200s until dried to obtain different magnetic layers, which were observed under a microscope.

[0088] Microscope images of magnetic layers prepared at different Fe3O4 concentrations are shown in Figure 2. Figure 7 As shown in the figure, the Fe3O4 concentrations corresponding to a~c are 10 mg / mL, 100 mg / mL and 600 mg / mL respectively. Figure 7 It shows that under the same conditions, after spin coating of 10 mg / mL Fe3O4 dispersion, the prepared robot has poor motion performance due to the low content of magnetic material. After spin coating of 600 mg / mL, visible aggregation occurs due to the high concentration, which is not suitable for the subsequent preparation of robots.

[0089] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for manufacturing a magnetically controlled micro-nano robot, characterized in that: The steps include: Coating a magnetic material dispersion solution on the surface of the substrate to form a magnetic layer; the magnetic material dispersion solution is a γ-butyrolactone solution of Fe3O4; the method of coating the magnetic material dispersion solution includes any one or more of spin coating, spray coating, roller coating, and brushing; A photoresist is coated on the surface of the magnetic layer and photolithography is performed to obtain a magnetically controlled micro-nano robot.

2. The method according to claim 1, characterized in that: In the magnetic material dispersed solution, the concentration of Fe3O4 is 20-500 mg / mL.

3. The method according to claim 1, characterized in that: The method of coating the magnetic material dispersion solution is spin coating.

4. The method according to claim 3, characterized in that: The spin coating speed is 100-1000 rpm.

5. The method according to any one of claims 1 to 4, characterized in that: Before coating the magnetic material dispersion solution on the substrate surface, the method further includes coating a sacrificial layer on the substrate surface.

6. The method according to claim 1, characterized in that: After the photolithography is completed, the method further includes a step of baking the magnetically controlled micro-nano robot.

7. The method according to claim 6, characterized in that: The temperature for baking the magnetically controlled micro-nano robot is 40-100°C.

8. A magnetically controlled micro-nano robot obtained by the manufacturing method according to any one of claims 1 to 7.

9. Application of the magnetically controlled micro-nano robot according to claim 8 in precision biomedicine, real-time sensor monitoring, micro-nano processing and manufacturing, pollution prevention and control, or environmental restoration.

Citation Information

Patent Citations

  • line reactor to protect rotating machines from overvoltage waves

    SU82005A1

  • Film forming method of induction material in deep groove

    CN104370266A

  • Magnetic packaged microrobot and preparation method thereof

    CN106517081A